Safety profiles of terahertz scanning in ophthalmology - Liu, Yu-Chi (2021)
Terahertz (THz) technology has emerged recently as a potential novel imaging modality in biomedical fields, including ophthalmology. However, the ocular biological responses after THz electromagnetic exposure have not been investigated. We conducted a rabbit study to evaluate the safety profiles of THz scanning on eyes, at a tissue, cellular, structural and functional level. Eight animals (16 eyes) were analysed after excessive THz exposure (control, 1 h, 4 h, and 1 week after continuous 4-h exposure; THz frequency = 0.3 THz with continuous pulse generated at 40 µW). We found that at all the time points, the corneas and lens remained clear with no corneal haze or lens opacity formation clinically and histopathologically. No thermal effect, assessed by thermographer, was observed. The rod and cone cell-mediated electroretinography responses were not significantly altered, and the corneal keratocytes activity as well as endothelial viability, assessed by in-vivo confocal microscopy, was not affected. Post-exposed corneas, lens and retinas exhibited no significant changes in the mRNA expression of heat shock protein (HSP)90AB1), DNA damage inducible transcript 3 (DDIT3), and early growth response (EGR)1. These tissues were also negative for the inflammatory (CD11b), fibrotic (fibronectin and α-smooth muscle actin), stress (HSP-47) and apoptotic (TUNEL assay) responses on the immunohistochemical analyses. The optical transmittance of corneas did not change significantly, and the inter-fibrillar distances of the corneal stroma evaluated with transmission electron microscopy were not significantly altered after THz exposure. These results provide the basis for future research work on the development of THz imaging system for its application in ophthalmology.